Affordances of School Ground Environments for Physical Activity: A Case Study on 10- and 12-Year-Old Children in a Norwegian Primary School - Lise Kjønniksen; Nora Wiium; Ingunn Fjørtoft (Frontiers Media S.A., 2022)
Several studies have focused on how different school ground environments can stimulate physical activity (PA) in children. This study aimed to investigate the contributions of two school ground environments (a constructed schoolyard and a natural forest) in moderate to vigorous physical activity (MVPA) of Norwegian school children in the 5th and 7th grades. This study described two school ground environments that provided large and multifunctional spaces, giving the children several affordances for being physically active during the school day. The constructed schoolyard afforded a space of 44 m2 per child and had an access to sports and game courts and various types of equipment for PA. The natural forest provided a space of 50.6 m2 per child and had a varied landscape for activities that afforded a wide range of PA. On average, the children engaged in 50% of the 60-min period of MVPA when playing in the natural and constructed play settings. The two different environments, thus, contributed equally to the daily MVPA of the school children. The findings can inform policies and programs aiming at promoting recommended levels of PA among children using school outdoor environments that may eventually have implications for the physical and mental health of school children during the current pandemic.